Alfabetização em questão: o reconhecimento do papel das cartilhas no percurso histórico do processo e a essencial ascensão do método fônico - Silva, Nayara Pâmella da (2020)
Analyzing the history of literacy in our country, we verify the great influence exerted by the spelling books , simple, precise and objective material, but which over the years lost value and fell into oblivion in the school sphere, however, it finds resistance in stationery stores, newsstands and homes. This fact is explained by the gap observed in our schools, alarming data indicate precariousness in teaching, high rates of illiteracy and lack of training for teachers. In that regard, the spelling books represent support for parents concerned with the difficulties presented by their children in the literacy process. The purpose of this material is to outline possibilities of work in the classroom so that the objective of literacy, from the perspective of literacy and in the light of linguistic knowledge, is achieved. Taking it into account, I present considerations on the need for the phonic method to be approached in the process, I outline the causes of the gap found by analyzing the methodology in force in our schools through the material Read and Write and rescue the contributions that the spelling books have brought throughout history for the literacy process. For the development of this work, I used bibliographic research, developed in a qualitative approach, of an exploratory-descriptive nature, using as a reference source the works of authors such as Mortatti, Soares, Cagliari and very particularly I used the notes made during the course. “Revisiting literacy” discipline taught by Prof. Dr. Luiz Carlos Cagliari at Universidade Estadual Paulista (UNESP), Araraquara campus.